2021
DOI: 10.1093/qjmed/hcab105.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of platelet gel in promoting healing of phalangeal fractures after fixation by Kirschner wires

Abstract: Background Autologous Platelet gel may become an ideal autologously prepared biologic blood-derived product that can be exogenously applied to a diversity of tissues, in which it releases high concentrations of platelet growth factors that enhance healing. Aim of the Work to evaluate the role of platelet gel in promoting healing in phalangeal fractures. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Only two studies to date tried to apply platelet gel alone to reconstruct bone defects and nonunions [ 51 , 60 ]. In these two studies, platelet gel was used alone, no other materials (such as bone graft) were mixed with platelet gel and no other treatment methods (such as extracorporeal shock wave therapy) were used in combination with platelet gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies to date tried to apply platelet gel alone to reconstruct bone defects and nonunions [ 51 , 60 ]. In these two studies, platelet gel was used alone, no other materials (such as bone graft) were mixed with platelet gel and no other treatment methods (such as extracorporeal shock wave therapy) were used in combination with platelet gel.…”
Section: Discussionmentioning
confidence: 99%
“…In a study presented by Sabbagh et al [ 60 ], the authors showed a positive treatment effect of using autologous platelet gel on promoting the healing of phalangeal fractures after fixation by Kirschner wires for 20 patients. In this study, platelet gel was used alone and was not mixed with bone graft or other materials.…”
Section: Research On Using Platelet Gel To Reconstruct Bone Defects A...mentioning
confidence: 99%